Relationship of Family Support and Accessibility with Elderly Following Activities Elderly Integrated Healthcare Center in Work Area Barong Tongkok Health Center Regency West Kutai - Wenda Feli Windra (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The increasing population of the elderly can cause several problems; therefore, it is necessary to have family support and accessibility that supports the elderly to be active and independent in maintaining and maintaining their health through Integrated Healthcare Center activities for the elderly.  Objective: To determine the relationship between family support and accessibility with the activity of the elderly attending the elderly Integrated Healthcare Center in the working area of ??the Barong Tongkok Health Center, West Kutai Regency.  Method: The research design in this research is analytical research method with Cross Selection approach.  Results and Discussion: There is a significant relationship between family support and the activity of the elderly attending the Integrated Healthcare Center for the elderly (value = 0.000); there is a significant relationship between the accessibility of the elderly with the activity of the elderly following the Integrated Healthcare Center for the elderly (value = 0.000).  Conclusion: There is a relationship between family support and accessibility with the activity of the elderly attending the Integrated Healthcare Center for the elderly in the working area of ??the Public Health Center Technical Implementation Unit Barong Tongkok, West Kutai Regency.